Talking horse Bernard Malamud on life and work - Malamud, Bernard 1914-1986 (Columbia Univ. Press, 1996)
Bernard Malamud, author of such acclaimed novels as The Fixer and The Natural and winner of two National Book Awards and a Pulitzer Prize, is widely recognized as one of the most important and enduring of American writers. Yet because he was intensely private about the way he worked, few readers are aware of his extraordinarily prolific expression of his commitment to the writing process. Including a wealth of never-before-published material, Talking Horse is designed to provide writers with insights into the way a master thought about and practiced his craft. This unique collection includes speeches, interviews, lesson plans, essays, and a series of previously unpublished notes on the nature of fiction, all of which offer an unparalleled look at the writing life. Each section of the book includes a headnote by Nicholas Delbanco or Alan Cheuse.
Keywords: Malamud, Bernard <1914-1986> - Critique et interprétation; Malamud, Bernard <1914->; Malamud, Bernard; Malamud, Bernard -- 1914-1986; Geschichte 1900-2000; Auteurschap; Juifs dans la littérature; Letterkunde; Roman américain - Histoire et critique - Théorie, etc; Roman juif - Histoire et critique - Théorie, etc; Literatur; American fiction -- History and criticism -- Theory, etc; Fiction -- Authorship; Jewish fiction -- History and criticism -- Theory, etc; Jews in literature; Novelists, American -- 20th century -- Biography; Interview; Quelle; Literaturproduktion; Biografie